Analisis Kinerja Kelompok Penyelenggara Pemungutan Suara (KPPS) dalam Pemilihan Umum Tahun 2019 di Kabupaten Tapanuli Utara - Ratama Ratama; Tonny P. Situmorang; Bengkel Ginting (PERSPEKTIF, 2023)
The role of Kelompok Penyelenggara Pemungutan Suara (KPPS) is one of the main keys in realizing voter sovereignty and has a very important role in the success of elections. This study observes that in carrying out their duties, the KPPS has experienced additional workload due to the addition of election ballots from the holding of simultaneous presidential and vice-presidential elections as well as legislative elections, this causes many KPPS’s members to become exhausted and even die as happened in North Tapanuli. This is the background for researchers in analyzing the performance of the KPPS of North Tapanuli and the factors that influenced their performance in the 2019 Election in North Tapanuli Regency. This study uses several theories such as Role, Performance, Workload and Democracy Theory. The research method is qualitative with a descriptive approach with the aim of analyzing information about the performance of the KPPS in the 2019 elections in North Tapanuli Regency based on the informants that the researchers grouped. The performance of the KPPS of North Tapanuli in general has been going well without any problems or lawsuits from the results of the voting and vote counting. On the other hand, Performance Indicators in this study are seen based on a focus on targets, quality, timeliness and accuracy. In addition, internal factors such as intellectuality, work experience, age, gender, health and educational background as well as external factors such as work environment, time and incentives also influence the performance of the KPPS of North Tapanuli.